Exposure of social structure in director Pa.Ranjith’s films - Poongulaly, S. (The 20th International Postgraduate Research Conference, 2019)
Cinema has played a role in caste and politics of India, Political mediation employed by the vetern actors will have to come to terms with its specific screen images. Specially Tamil cinema has always been in a constant struggle to eradicate as well as to maintain the boundaries between the dominant and the dominated. There are many directors in the cinema field; within them some are getting the in-depth place among their viewers. In that way director Pa.Ranjith has carved a niche for himself by bringing social and political realities of contemporary Tamil Nadu into mainstream cinema. His films do not compromise on his politics and show a natural progression of political discourse on the life of Dalits and other marginalized communities. This paper deals with the analysis of director Pa.Ranjith’s four films Attakathi (Cardboard knife) (2012), Madras (2014), Kabali (2016), and Kaala (2018). This researcher’s main purpose is to find out the way of exposing social structure throughout his four films and to find out what strategies are being used by the director to expose the structure. The hypothesis of this research is the four films of director Pa.Ranjith represents social structure through their screening, characterization, languages and even with colors also. The film Attakathi is a light-hearted romantic comedy which won critical acclaim for its honest and realistic treatment. Film Madras depicts life in north Chennai, and it revolves a wall and how two political parties lay their claim to it. The film Kabali concerns the gang war between the protagonist and antagonist who attempts to protect his family from enemies, gained in his time as a gangster. Kaala A resident of Dharavi unites the people living in his area to stand up against a ruthless politician who dreams of taking over their land. The descriptive content analysis with semiotic approach, and in-depth interviews used as the study methodology. Secondary data has been used as sources. The cultivation theory and auteur theory have been used to analyze the theoretical framework. As in the conclusion, the symbols and colors were used as main strategies to expose the social structure including the caste, status, differentiation and challenges of middle-class people by director.
Keywords: Social structure; Theme; Director; Setting of films; Caste and politics